Brief communication: Sea-level projections, adaptation planning, and actionable science - W. H. Lipscomb; D. Behar; M. A. Morrison (The Cryosphere)
As climate scientists seek to deliver actionable science for adaptation planning, there are risks in using novel results to inform decision-making. Premature acceptance may lead to maladaptation, practitioner confusion, and “whiplash”. We propose that scientific claims should be considered actionable (i.e., sufficiently accepted to support near-term adaptation action) only after meeting a confidence threshold based on the strength of evidence as evaluated by a diverse group of scientific experts. We discuss an influential study that projected rapid sea-level rise from Antarctic ice-sheet retreat but in our view was not actionable. We recommend regular, transparent communications between scientists and practitioners to support the use of actionable science.